Open Polar: a discovery service covering the global output of openly accessible polar research data and publications - Abu-Alam, Tamer S.; Aspaas, Per Pippin; Longva, Leif Longva; Nilsen, Karl Magnus; Odu , Obiajulu (Septentrio Conference Series, 2020)
Data from the Polar Regions are of critical importance to modern polar research. Regardless of their disciplinary and institutional affiliations, researchers rely heavily on the comparison of existing data with new data sets to assess changes that are taking effect. However, in a recent survey of 113 major polar data providers, we found that an estimated 60% of the existing polar research data is unfindable through common search engines and can only be accessed through institutional webpages. Moreover, a study by Johnson et al. (2019) showed that in social science and indigenous knowledge, the findability gap is around 84%. This results in an awareness of the need of the scientific community to harvest different metadata related to the Polar Regions and collect these in a homogenous, seamless database and making this database available to researchers, students and the public through one search platform.This contribution describes the progress in an ongoing project, Open Polar (https://site.uit.no/open-polar/) started in 2019 at UiT The Arctic University of Norway. The project aims to collect metadata about all the open-access scholarly data and documents related to the Polar Regions in a homogenous and seamless database. The suggested service will include three parts: 1) harvesting metadata; 2) enriching and filtrating of the harvested metadata relevant to Polar Regions; and 3) making the collected records available and searchable to the end-users through an interactive user interface. The service will help to make the polar related research data and documents more visible and searchable to the end-users and thereby reducing the findability gap.
Keywords: Open Polar; Research data; open access